Design of an assistive-rehabilitative walker for children with cerebral palsy - Anuar A.; Selvam T.P.; Mahamud F. (Asian Research Publishing Network, 2023)
Cerebral palsy (CP) is a disorder which is caused by brain damage. Most of the cerebral palsy children cannot walk on their own. They need an assistive or rehabilitative walking device to help them to walk, however most of these devices are either single- functional and/or expensive. This paper describes the design of a multifunctional and relatively affordable assistive-rehabilitative walker. The design requirements were developed from discussion and interview with CP children and their caregivers. The designed walker has four configuration modes which are standing and walking mode, ground-sitting mode, wheelchair mode and exercise mode. Analysis was conducted to ensure the design is safe to be used, and the design was fabricated. The fabricated prototype was tested with a cerebral palsy child. Four different tests were conducted with the prototype where the child managed to use the walker for the intended purposes. 2006-2016 Asian Research Publishing Network (ARPN).